Dampak Pandemi Covid-19 : Studi Kasus Kemiskinan dan Ganggunan Kesehatan Mental di Kapanewon Seyegan, Sleman, DIY - Nur Faidati; Suci Iriani Sinuraya (Prosiding University Research Colloquium, 2021)
This study intends to analyze the impact of the Covid-19 pandemic on poverty and mental health. Covid-19 has been going on for almost 2 years. This condition has an impact on the community's economy and other social problems, just like mental health . Some people have lost their livelihoods, their businesses have declined and some have even failed. This further worsens the condition of Kapanewon Seyegan which has the highest poverty rate in Sleman Regency. The research method used in this study is a qualitative research method. This research was conducted in Kapanewon Seyegan, Sleman Regency, between June – August 2021. Based on the research conducted, the pandemic has worsened poverty conditions in Kapanewon Seyegan. Furthermore, the pandemic also causes other problems such as the addition of ODGJ cases and a number of other problems. To respond to this problem, it is necessary to carry out community empowerment activities that can have an economic impact as well as community empowerment related to providing support to the ODGJ community and farmer groups.